Hydroxychloroquine-induced auditory toxicity - Abhishek Patil; Yapi Jerang; John Mathew (Indian Journal of Rheumatology)
A 51-year-old female with mixed connective tissue disease presented with bilateral sensorineural hearing loss. The hearing deficit was gradually progressive over a period of 6 months. On evaluation, no obvious cause for hearing was evident. Due to ototoxic potential of hydroxychloroquine, we decided to stop the drug and observe for improvement. Over time, her hearing loss stabilized, with improvement in audiometric findings. Hydroxychloroquine induced auditory toxicity is rare. Increased awareness and early recognition may minimize damage.